Thickness and relative hyperbolicity for graphs of multicurves. Issue 4 (31st October 2022) - Russell, Jacob; Vokes, Kate M.
Abstract: We prove that any graph of multicurves satisfying certain natural properties is either hyperbolic, relatively hyperbolic, or thick. Further, this geometric characterization is determined by the set of subsurfaces that intersect every vertex of the graph. This extends previously established results for the pants graph and the separating curve graph to a broad family of graphs associated to surfaces.